2019
DOI: 10.5603/cj.a2019.0094
|View full text |Cite
|
Sign up to set email alerts
|

Calcific lesion preparation for coronary bifurcation stenting

Abstract: Bifurcating coronary lesions are a very common challenge in interventional cardiology because of the technical complexity in their treatment, the risk of side branch occlusion and an overall worse outcome when compared to non-bifurcating lesions. The presence of calcifications represents further complexity due to the difficulty in device delivery and stent expansion as well as enhanced risk of side branch occlusion. Rotational and orbital atherectomy, scoring and cutting balloons, coronary lithoplasty are avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Numerous strategies aiming at the appropriate preparation of calcified plaques have been implemented [1]. The two main techniques include the balloon-depended and the atherectomy devices.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous strategies aiming at the appropriate preparation of calcified plaques have been implemented [1]. The two main techniques include the balloon-depended and the atherectomy devices.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, patients with diffuse long lesions may tend to be treated with more stents with longer stent lengths, rendering them more prone to stent under‐expansion and mal‐apposition, target vessel revascularization, or stent thrombosis 14–16 . Several studies showed that a bifurcation lesion and its relevant stent implantation in both branches also increases the risk of MI and stent thrombosis 17,18 . Likewise, patients undergoing PCI with CTO have a higher rate of adverse ischemic events 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Fujino et al demonstrated that the presence of coronary calcification at the site of a bifurcation assessed by optical coherence tomography is associated with a higher risk of side branch occlusion [ 19 ]. In this context, the main issues to provide optimal vessel patency are careful lesion preparation to “soften” the lesion, prevention of plaque shifting, and careful carina reconstruction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%